Applying Structural Equation Model To Develop A New Model Of Happiness At The Workplace In Promoting Employee Happiness In Public Organization - Al-Shami, Samer Ali Hussein; Al Suwaidi, Essa Yousuf Majid; Akmal, Suriati (Semnan University, Center of Excellence in Nonlinear Analysis and Applications, 2020)
Happiness at the workplace refers to how satisfied people are with their workplace and lives. Happy people are productive people while those people who are unhappy may not pay full attention to any task. Furthermore, employees in the public organizations in UAE are not well satisfied due to poor workplace conditions. In some ministries in UAE must equipment are not well maintained to ease the work of an employer. The main aim of this paper to develop a Model of happiness at the workplace in promoting employee happiness in public organization using structural equation Model. The data were obtained from the employee of Dubai Electricity and Water Authority in UAE. Since the population of this study is 11787 therefore, the sample size was 370. surveyed through the self-administered Google form and by posting. The data was screened, and out of the 370 questionnaires distributed, 260 were completed and were received. Analysis of Moment Structures (AMOS) in Structural Equation Modelling (SEM) confirmatory factor analysis (measurement and structural measurement models) were used to analyzed the data. Although this study has conceptualized the improving happiness at the workplace in promoting employee happiness in public organization. Additional research is needed among other states in UAE such Dubai. The motivational formulation of employee happiness, job involvement, work place climate and its impact on organizational performance is a point of future research.